2004
DOI: 10.1289/ehp.6841
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors and Susceptibility to Arsenic-Caused Skin Lesions in West Bengal, India

Abstract: There has been widespread speculation about whether nutritional deficiencies increase the susceptibility to arsenic health effects. This is the first study to investigate whether dietary micronutrient and macronutrient intake modulates the well-established human risk of arsenic-induced skin lesions, including alterations in skin pigmentation and keratoses. The study was conducted in West Bengal, India, which along with Bangladesh constitutes the largest population in the world exposed to arsenic from drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(107 citation statements)
references
References 16 publications
2
104
0
Order By: Relevance
“…Patients with protein-energy malnutrition have inadequate supply of methionine from dietary sources, and studies in rabbits have shown low amount of methionine or protein in the diet decreased methylation of inorganic arsenic [30]; and deficiency of other dietary trace elements including zinc and selenium [31] may lead to arsenic accumulation and contribute to the toxic effects in the body. A recent study has shown that low intake of calcium, animal protein, folate and dietary fiber may increase susceptibility to arseniccaused skin lesions [32]. Moreover, apart from the poor nutritional status, peoples in Bangladesh have greater daily intake of water (and thus consume more arsenic) than those living in other parts of the world that are not tropical, and thereby suffer from the adverse effects of arsenic toxicity.…”
Section: Number Of Patients With Clinical Symptomsmentioning
confidence: 99%
“…Patients with protein-energy malnutrition have inadequate supply of methionine from dietary sources, and studies in rabbits have shown low amount of methionine or protein in the diet decreased methylation of inorganic arsenic [30]; and deficiency of other dietary trace elements including zinc and selenium [31] may lead to arsenic accumulation and contribute to the toxic effects in the body. A recent study has shown that low intake of calcium, animal protein, folate and dietary fiber may increase susceptibility to arseniccaused skin lesions [32]. Moreover, apart from the poor nutritional status, peoples in Bangladesh have greater daily intake of water (and thus consume more arsenic) than those living in other parts of the world that are not tropical, and thereby suffer from the adverse effects of arsenic toxicity.…”
Section: Number Of Patients With Clinical Symptomsmentioning
confidence: 99%
“…Low intake of calcium, animal protein, folate and fiber may increase susceptibility to arsenic-caused skin lesions (Mitra et al, 2004). The potential of dietary antioxidants (vitamin C, E and β-carotene) may reduce the arsenic burden in human by increasing its metabolism (Dey, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested a strong association between poor nutritional status with clinical manifestations of chronic arsenicosis, resulted less detoxification in the liver and impaired urinary elimination of arsenic ; Haque et al, 2003;Mitra et al, 2004).…”
Section: Introductionmentioning
confidence: 99%